Tramas da (ir)racionalidade contemporânea para a composição do mito-tecno-lógico - Pires, João Maria (2004)
The plot myth-techno-logic, contemporary, was developed starting from the dualism myth-reason. In this study, we deepened the alluded dualism taking as reference the historical contexts of the Renaissance and of the Enlightenment, emphasizing the discussion of the economical rationalization as conductive thread of the western development, in which we identified the game of the rational and of the irrational, for assure the superiority of the reason. In the context of that game, we analyzed the implications of the modernization, for the education, in function of the instrumental rationality, responsible for the environment of adaptation of the technological instruments to the scenery of the contemporary modernization. The new context is constituted by points of union and of ruptures among the technique, the science and the myth. Through our analysis, we noticed that the basic needs for the contemporary society were linked to the changes in the production means, for which the machine determine the rhythm of the work and the quality of the product. However, the changes in the productive processes promoted the appearance of the commercial marks that, as we see it, they represented the synthesis of the perfect harmony of the myth, of the technique, of the science and of the technology, in the conduction of the economical rationalization to the contemporary modernization. Thus, the contemporary modernization it arrives us for the economical rationalization, developed with the support of the technician-scientific knowledge and communicated by the articulations of the myth-techno-logical